Systematic review of teacher well-being research during the COVID-19 pandemic - Aziku, Millicent; Zhang, Baohui (Frontiers in Psychology, 2024)
The current systematic review through quantitative method aims to analyze the distribution of teacher well-being research from 2020 to mid-February 2024, focusing on the yearly research distribution of studies, the research methods adopted by scholars and the group of teachers investigated over the period. The PRISMA guidelines were followed and 103 empirical studies were selected for the analysis. The review shows notable rise in research, particularly in 2022 and 2023 representing (37.9%) and (35.9%) respectively. This suggests a growing interest in teacher well-being among educational researchers. The findings also indicate that, researchers mostly adopted quantitative method in the form of survey (79.6%) for studies on teacher well-being. However, there has been an increase in qualitative and mixed method research recently (9.7%) and (10.7%) respectively. The review also identified that focus had been placed on teachers in general (55.3%) than specific group of teachers. The review suggests that, it is advisable to adopt more mixed method research to enhance the understanding of teacher well-being factors at all levels of education. This review contributes to the extensive knowledge on teacher well-being research field.